Mechanisms of Endothelial Dysfunction in Pre-eclampsia and Gestational Diabetes Mellitus: Windows Into Future Cardiometabolic Health? - McElwain, Colm J.; Tuboly, Eszter; McCarthy, Fergus P.; McCarthy, Cathal M. (Frontiers in Endocrinology, 2020)
Placental insufficiency and adipose tissue dysregulation are postulated to play key roles in the pathophysiology of both pre-eclampsia (PE) and gestational diabetes mellitus (GDM). A dysfunctional release of deleterious signalling motifs can offset an increase in circulating oxidative stressors, proinflammatory factors and various cytokines. It has been previously postulated that endothelial dysfunction, instigated by signalling from endocrine organs such as the placenta and adipose tissue, may be a key mediator of the vasculopathy that is evident in both adverse obstetric complications. These signalling pathways also have significant effects on long term maternal cardiometabolic health outcomes, specifically cardiovascular disease, hypertension, and type II diabetes. Recent studies have noted that both PE and GDM are strongly associated with lower maternal flow-mediated dilation, however the exact pathways which link endothelial dysfunction to clinical outcomes in these complications remains in question. The current diagnostic regimen for both PE and GDM lacks specificity and consistency in relation to clinical guidelines. Furthermore, current therapeutic options rely largely on clinical symptom control such as antihypertensives and insulin therapy, rather than that of early intervention or prophylaxis. A better understanding of the pathogenic origin of these obstetric complications will allow for more targeted therapeutic interventions. In this review we will explore the complex signalling relationship between the placenta and adipose tissue in PE and GDM and investigate how these intricate pathways affect maternal endothelial function and, hence, play a role in acute pathophysiology and the development of future chronic maternal health outcomes.